DPM-based method for tracking maneuvering targets in wireless sensor networks - LIN Jin-zhao1; LI Guo-jun2; ZHOU Xiao-na2; ZHOU Dao-jun 2; JIANG Yong 2 (Tongxin xuebao)
Focused on energy efficiency issues under tracking targets within WSN,a new dynamic power management（DPM） method for tracking distributed targets was proposed combining with the network energy consumption model and wake-up mechanism.With precedent location information of maneuvering target,the algorithm involved both cancelling noise by wavelet filter and predicting target state by autoregressive transformation is introduced to awaken wireless sensor nodes so that their sleep time is prolonged and energy consumption is reduced.According to the current location of maneuvering target,related nodes in an appointed cluster of WSN constitute a distributed dynamic tracking unit,and the cluster head is responsible for collecting the measurement information from the nodes in the tracking unit.A locating algorithm based on the relative posi-tion of two circulars formed on the bases of measurement information is adopted to simplify the process of locatiny and tracking target.Simulation results show that the DPM-based method can reduce the nodes’ energy consumption,meet the locating and tracking accuracy,and can be applied to locate and track the maneuvering targets on the earth surface.